The Strategic Repositioning of the European Union Consumers in the Context of the Energy Paradigm Change. From the Traditional Supplier-User Relationship to the Emergence of the Prosumers - Dumitru Miron; Vlad Epurescu; Elisabeta Andreea Budacia (Amfiteatru Economic, 2023)
The entire contemporary societal landscape, including the business environment, faces a complex kaleidoscope of challenges, fuelled by a greater than ever level of turbulence manifesting itself on all levels. In the new circumstances, opportunities and threats follow and multiply, interfere, and require a proactive approach and placed in synergistic logic. We are witnessing the emergence of times in which the most frequently used term is resilience. At the level of the European Union, resilience can be attached to all strategic or tactical vectors, the most interesting areas of manifestation of the need for resilience being those related to digitisation and the energy sector. Starting from the hypothesis that most of the geopolitical and geoeconomic conditions are changing at a very high speed, the authors of this article proposed to emphasise aspects related to the rediscovery of the advantages of energy autonomy. Aggregating the production curves for dispatchable photovoltaic energy in 2021, at the national level, the authors also highlighted a production model for prosumers. In this context, using the Cobb-Douglas production function, an attempt was made to diagnose the conditions in which the consumer can have a versatile role and become, in turn, an energy producer, contributing to the climate agenda.
Keywords: D11; D24; O30; 330; Prosumers; renewable energy; photovoltaic energy; prosumption; energy suppliers.